Empowering Citizens through Budget Transparency in the North-West and Adamawa Regions - Agarwal, Sanjay (World Bank, Washington, DC, 2014)
Citizens often lack information on the use of public funds. They are usually left out of allocation decisions and do not have opportuni¬ties to provide adequate and timely feedback on the use of scarce resources. Transparency in budgetary processes reduces opportu¬nities for wasteful and corrupt spending. As a consequence, and because it can increase trust in authorities and lead to enhanced tax collections, budget transparency could increase resources avail¬able to fight poverty. Therefore, with support from the World Bank, two regions in Cameroon (the North-West and Adamawa) piloted an initiative to promote greater budget transparency with three objectives: simplification, analysis, and disclosure of budgets at multiple levels (national, regional, divisional, municipal, school, and health center); awareness and capacity-building of government officials and local/regional institutions to promote public dialogue about public expenditures by encouraging demand-side governance; and documentation and dissemination of activities. In both the regions, steering committees under the chairman¬ship of their governors spearheaded and coordinated the activities under the initiative. Two local nongovernmental organizations with expertise in social accountability approaches facilitated the community mobilization and budget dissemination process.